Quantification of the influence of the track geometry variability on the train dynamics. (August 2015) - Perrin, G.; Duhamel, D.; Soize, C.; Funfschilling, C.
Abstract: In a context of increasing interoperability, several high speed trains are likely to run on the same tracks, whereas they have been originally designed for specific railway networks. Due to different mechanical properties, the dynamic behaviors of the vehicles will be very different from one train to another. The track-vehicle system being strongly non-linear, the dynamic interaction between the vehicle and the railway track has moreover to be analyzed not only on a few track portions but on the whole realm of possibilities of running conditions that the train can be confronted to during its life cycle. The idea of this paper is therefore to show to what extent this influence of the track geometry variability on the train dynamics can be analyzed from the coupling of a deterministic multibody modeling of the train with a track geometry stochastic modeling, which has been identified and validated from experimental data. Abstract : Highlights: A method to propagate the railway track variability to the train dynamics is presented. This model couples a rigid body modelling of the train with a track geometry stochastic modelling. The method is validated by comparisons to experimental data. Three applications illustrate the whole method.